Morphology and multigene phylogeny reveal a new species and a new record of saprobic Dothideomycetes from Hevea brasiliensis in Yunnan Province, China - Xu, Rui-Fang; Karunarathna, Samantha C.; Hyde, Kevin D.; Kakumyan, Pattana; Dai, Dong-Qin; Elgorban, Abdallah M.; Phukhamsakda, Chayanard; Tibpromma, Saowaluck (Phytotaxa, 2025)
Hevea brasiliensis (Para rubber) is an important crop that produces a milky, white fluid called “natural rubber” and is one of the economic plants in the Greater Mekong region. Among the Greater Mekong Region countries, China has received little attention to the saprobic fungi associated with rubber. In our survey of saprobic fungi associated with rubber plants in Yunnan Province, China, we collected and isolated two types of ascomata on dead rubber branches and identified them based on phylogenetic analyses of ITS, LSU, SSU, tef1-α, and rpb2 sequence data and morphological characteristics. The results revealed one previously unknown taxon (Anthosulcatispora heveae) and a new host and country record (Anteaglonium parvulum) on Hevea brasiliensis in Yunnan Province, China. The new species has a unique morphology of fusiform, hyaline ascospores with large guttules and mucilaginous sheath compared with similar species in Anthosulcatispora. The descriptions, illustrations, and phylogenetic analysis results of the two taxa are provided.